2019
DOI: 10.1002/aocs.12290
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Epoxidized Hemp Oil Prepolymers for the Preparation of Thermoset Networks

Abstract: Epoxy thermosets comprised of plant oils along with simple curing agents are sustainable and environmentally friendly polymers. The curing agent selected, and its compatibility with epoxy monomers, strongly affects the curing kinetics, the extent of curing, and the final properties of an epoxy polymers. The goal of this work is to expand the application of epoxidized oils in formulating biobased thermoset polymer systems. Epoxidized hemp oil (EHO) was produced with 8% oxirane oxygen content (OOC) after 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Detailed interpretations of the FTIR spectra of plant oils and oil derivatives can be found in the literature. 27,44 For LO, Figure 3 shows the C�C−H double bond stretch at 3006 cm −1 and C�C vibrations at 1655 cm −1 ; these disappear in the epoxidized oil derivatives. The transformation of double bonds into epoxy groups is confirmed by the appearance of the new band at 826 cm −1 , which corresponds to the C−O−C stretching from the oxirane vibration.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed interpretations of the FTIR spectra of plant oils and oil derivatives can be found in the literature. 27,44 For LO, Figure 3 shows the C�C−H double bond stretch at 3006 cm −1 and C�C vibrations at 1655 cm −1 ; these disappear in the epoxidized oil derivatives. The transformation of double bonds into epoxy groups is confirmed by the appearance of the new band at 826 cm −1 , which corresponds to the C−O−C stretching from the oxirane vibration.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the nontechnical challenges, the authors of this manuscript feel that the technical challenges that face the development of cannabis-based bioproducts are much more readily apparent as they incorporate many of the same issues that face other bioproducts. For example, like other plant oils, hemp seed oil has a high oxygen content which in turn makes it susceptible to oxidation. , Other technical challenges facing cannabis, which are also common to other biorefinery crops, include ensuring uniformity of feedstock and reducing overall water and energy consumption. In light of the above, the authors have identified the following specific technical opportunities:…”
Section: Challenges and Opportunities In The Development Of Hemp-base...mentioning
confidence: 99%
“…Omonov et al 33 blended epoxidized hempseed oil with one of two different curing agents (trimetallic anhydride (TMA) and citric acid (CA)) in order to prepare epoxy thermosets. Compared to the processes used by Surender et al 122 and Shuttleworth et al 123 the process used by Omonov et al 26 differed mainly in the choice of curing agents.…”
Section: Solid Materials From Hempmentioning
confidence: 99%
See 2 more Smart Citations